The Relationship Between Person-Major Congruence and Successful Grade Achievement at Universitas Pendidikan Indonesia - Sasi, Khamila; Windhu, Triyatmoko; Vlarissa, Vlarissa; Rizkyanfi, Mochamad Whilky (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2023)
The person-majors fit plays a significant role in the success of the grades achievement of each student. This study aims to determine the relationship between the person-majors chosen by students and the grades obtained after finishing their education. This research took place at the University of Education Indonesia, especially for students majoring in Psychology. The research method uses a one-short model approach which means carried out through one-time data collection using google form media. The research population was 150 UPI Psychology students in 2022—sampling using a random sampling technique. The findings showed (1) 96.8% were in fit with the chosen major, 3.2% were not in fit with the chosen major; (2) 25.8% were satisfied with the results of the value acquisition, 74.2% were not satisfied with the results of the grade achievement. The analysis revealed a relationship between the person-major fit and grade success that positively influences learning performance. Recommendations and suggestions for future researchers are to enlarge the scope of research so that a broader scope of research can be obtained.